CeO2 nanoparticle morphologies and their corresponding crystalline planes for the photocatalytic degradation of organic pollutants - Amoresi, Rafael Aparecido Ciola [UNESP]; Oliveira, Regiane C. [UNESP]; Longo, Elson [UNESP]; Sambrano, Julio Ricardo [UNESP]; Marana, Naiara Letícia [UNESP]; Almeida, Priscila Bonfochi de [UNESP]; Prata, Paloma Santana; Zaghete, Maria Aparecida [UNESP]; Simões, Alexandre Zirpoli [UNESP] (ACS Publications, 2019)
Currently, numerous properties of semiconducting oxides are correlated to their morphological characteristics resulting from their exposed surfaces. In the present work, the relationship between the following morphologies rod, bean, hexagon, and rod/cube of CeO2 with the exposure of (111), (110), (100), and (311) surfaces and the main charge carriers generated by the photochemical processes was investigated. This was done in regard to the degradation of ciprofloxacin and rhodamine-B. The initial stages of the degradation of the two types of molecules were evaluated, allowing the determination of where the charge carriers generated in the semiconductor preferentially acted on the molecules. Therefore, the active species in each photocatalyst were identified by scavenger tests and correlated to the computational simulations using the density functional theory. Accordingly, the relationships between the morphology, surface exposure in the particles, surface defects, photochemically generated species, and preferential attack on the micropollutant molecule were shown. Specific surface area analyses demonstrate an effective relationship between photocatalytic activity and the exposed surface of the particle. This will allow rationalization of the relation between the catalytic and electronic properties of semiconductor surfaces.
CeO2 Nanoparticle Morphologies and their corresponding crystalline planes for the photocatalytic degradation of organic pollutants
Keywords: Surface; Scavengers; CeO2; Superfícies; CIP; DFT